RECURSO DE TECNOLOGIA ASSISTIVA PARA ESTUDANTES COM PARALISIA CEREBRAL: JOGO DE DAMAS ADAPTADO COMO MODELO METODOLÓGICO: - Campos, Jessenia Marise Sales [UNESP]; Seabra, Manoel Osmar [UNESP]; Santos, Talita Maria Souza [UNESP]; Romero, Luiz Rogerio [UNESP] (Faculdade de Filosofia e Ciências, 2024)
This study aimed to analyze the effects of the board game “Adapted Checkers” on the performance of manipulative skills in a student with cerebral palsy. The study identifies and describes the adaptations of teaching strategies and implementation of the Assistive Technology pedagogical resource. The method used was the single-subject design, in the AB model. The design demonstrates the student's performance in relation to manipulative skills, as dependent variables, and the game of “Adapted Checkers” as an independent variable. The research was divided into the following stages: 1. Choice of game: the board game Checkers was chosen, which met the criteria established in the research and the characteristics of the student with cerebral palsy; 2. Baseline: where the initial data collection began without researcher intervention; 3. Adaptation of the game: the game was adapted based on the specific needs of the participant; 4. Intervention: introduction of strategies and adaptations to the game. The sessions were filmed, and the data were evaluated and recorded in scatter plots. For data analysis, a table of response variables was used, scored from zero to three points. The items evaluated were: 1. Precision of movement; 2. Range of movement; 3. Handgrip ability; and 4. Speed of movement. The participant showed significant progress in all variables through training in the intervention phase, with the resource adaptations. The game of “Adapted Checkers” was shown to be effective in relation to the manipulative skills of the student with cerebral palsy, providing autonomy during the game. Received: 2024/04/19 Reformulated: 2024/06/03 Accepted: 2024/06/11 Este estudo tem como objetivo analisar os efeitos do jogo de tabuleiro “Damas Adaptado” sobre o desempenho de habilidades manipulativas de uma estudante com paralisia cerebral. O estudo identifica e descreve as adaptações de estratégias de ensino e implementações no recurso pedagógico como Tecnologia Assistiva. O método utilizado foi o delineamento do sujeito único, no modelo AB. O delineamento demonstra o desempenho da estudante frente as habilidades manipulativas, denominadas variáveis dependentes e o jogo de “Damas Adaptado” como variável independente. A pesquisa foi dividida nas seguintes etapas: 1. Escolha do jogo: foi escolhido o jogo de tabuleiro Damas, que atendeu os critérios estabelecidos na pesquisa e características da estudante com paralisia cerebral; 2. Linha de base: onde se iniciou as primeiras coletas de dados sem intervenção do pesquisador; 3. Adaptação do jogo: jogo adaptado a partir das necessidades específicas da participante; 4. Intervenção: introdução das estratégias e adaptações no jogo. As sessões foram filmadas, os dados avaliados e registrados em gráficos de dispersão. Para a análise dos dados, foi utilizado um quadro de variáveis de respostas que pontuavam de zero a três pontos, onde os itens avaliados foram: 1. Precisão do movimento; 2. Amplitude de movimento; 3. Capacidade preensão palmar e 4. Velocidade do movimento. A participante obteve evolução significativa em todas as variáveis por meio do treinamento, na fase de intervenção com as adaptações do recurso. O jogo de “Damas Adaptado” se demonstrou eficaz em relação às habilidades manipulativas da estudante com paralisia cerebral, proporcionando autonomia durante o jogo. Recebido em: 19/04/2024Reformulado em: 03/08/2024Aceito em: 11/06/2024